2020
DOI: 10.3390/jcm9103066
|View full text |Cite
|
Sign up to set email alerts
|

The PANDEMYC Score. An Easily Applicable and Interpretable Model for Predicting Mortality Associated With COVID-19

Abstract: This study aimed to build an easily applicable prognostic model based on routine clinical, radiological, and laboratory data available at admission, to predict mortality in coronavirus 19 disease (COVID-19) hospitalized patients. Methods: We retrospectively collected clinical information from 1968 patients admitted to a hospital. We built a predictive score based on a logistic regression model in which explicative variables were discretized using classification trees that facilitated the identification of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 18 publications
3
51
0
4
Order By: Relevance
“…The important characteristics and outcomes of the included articles were collated (Table 1). Of 40 articles, 19 were conducted in China 21,22,27,29,30,[37][38][39][40][41][42][43][44][45][46][47][48][49][50] , one in Kuwait 26 , one in Korea 28 , one in Mexico 51 , one in Japan 52 , two in Spain 53,54 , three in Italy [55][56][57] , and twelve in the USA 33,[58][59][60][61][62][63][64][65][66][67][68] . Most articles were retrospective studies.…”
Section: Search Results and Characteristics Of Studies Includedmentioning
confidence: 99%
See 1 more Smart Citation
“…The important characteristics and outcomes of the included articles were collated (Table 1). Of 40 articles, 19 were conducted in China 21,22,27,29,30,[37][38][39][40][41][42][43][44][45][46][47][48][49][50] , one in Kuwait 26 , one in Korea 28 , one in Mexico 51 , one in Japan 52 , two in Spain 53,54 , three in Italy [55][56][57] , and twelve in the USA 33,[58][59][60][61][62][63][64][65][66][67][68] . Most articles were retrospective studies.…”
Section: Search Results and Characteristics Of Studies Includedmentioning
confidence: 99%
“…Nineteen studies defined outcomes as disease severity 22,[27][28][29][30][37][38][39]42,43,[46][47][48][49][50]58,60,62,63 . Seventeen studies defined outcomes as death 21,33,40,44,45,[51][52][53][54][55][56][57]59,[65][66][67][68] . Four studies used both disease severity and death 26,41,61,64 .…”
Section: Search Results and Characteristics Of Studies Includedmentioning
confidence: 99%
“…Early identification in the ED of patients with COVID-19 disease who may develop critical illness, and therefore require hospital admission is of great importance, as it allows selecting patients who might benefit from an outpatient care model and thereby optimize the use of resources [ 17 19 ]. An integrated emergency—medical care at home system as an intermediate approach between outpatient control in primary care and hospital admission, is a new model for the management of cases of mild pneumonia in an overloaded health care system [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PANDEMYC score 5 showed that oxygen saturation was an important discriminatory factor in predicting survival or in-hospital deterioration.…”
Section: Discussionmentioning
confidence: 99%